Evaluation of calf milk pasteurization systems on 6 Pennsylvania dairy farms - Elizondo Salazar, Jorge Alberto (2010)
Waste milk has been fed to calves for many years, but concerns with bacterial contamination as well as possible transmission of diseases have discouraged widespread use of this feed. Pasteurization of waste milk is one option to reduce management risk while utilizing a valuable, low-cost, liquid feed source for calves. However, many farms currently pasteurizing waste milk lack a system to adequately monitor the efficiency of the process. A study was carried out to evaluate 6 on-farm pasteurization systems, including high-temperature, short-time pasteurizers and low-temperature, batch pasteurizers. Milk samples were taken pre- and postpasteurization as well as from the calf buckets and immediately frozen for later bacterial culture. Samples were collected twice daily for 15 d. Milk samples were examined for standard plate count (SPC), coagulase-negative staphylococci count, environmental streptococci count, coliform count, gram-negative noncoliform count, Streptococcus agalactiae count, and Staphylococcus aureus count. Before pasteurization, 68% of the samples had SPC <20,000 cfu/mL, and 39% of samples contained <100 cfu/mL of coliform bacteria. After pasteurization, 96% of samples had SPC <20,000 cfu/mL, and 92% had coliform counts <100 cfu/mL. Bacteria counts were significantly reduced by pasteurization, and pasteurized milk contained acceptable numbers of bacteria in >90% of samples. These results indicate that pasteurization can be very effective in lowering bacterial contamination of milk. However, bacteria numbers significantly increased after pasteurization and, in some cases, bacteria counts in milk fed to calves were similar to prepasteurization levels. Milk handling after pasteurization was identified as an important issue on the farms studied.